2022
DOI: 10.1038/s41598-021-03748-0
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of VLA4 in multiple myeloma cells redirects tumor spread and prolongs survival

Abstract: Multiple myeloma (MM) is a cancer of bone marrow (BM) plasma cells, which is increasingly treatable but still incurable. In 90% of MM patients, severe osteolysis results from pathological interactions between MM cells and the bone microenvironment. Delineating specific molecules and pathways for their role in cancer supportive interactions in the BM is vital for developing new therapies. Very Late Antigen 4 (VLA4, integrin α4β1) is a key player in cell–cell adhesion and signaling between MM and BM cells. We ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…were examined by flow cytometry using LLP2A-Cy5 (19). Using a 14-color flow cytometry panel, we identified eighteen different hematopoietic cell populations within these seven samples (Supplemental Figure 8).…”
Section: Flow Cytometry Studymentioning
confidence: 99%
See 2 more Smart Citations
“…were examined by flow cytometry using LLP2A-Cy5 (19). Using a 14-color flow cytometry panel, we identified eighteen different hematopoietic cell populations within these seven samples (Supplemental Figure 8).…”
Section: Flow Cytometry Studymentioning
confidence: 99%
“…Purified cells were > 97% for CD38 + CD138 + plasma cells. LLP2A-Cy5 synthesis and flow cytometry were performed as previously described (19) IGS mice and was considered NOEL (no observable effect level) (Supplemental Figure 4).…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The VCAM-1 ligand, very-late antigen 4 (VLA-4), is frequently overexpressed on malignant plasma cells in the BM and plays an important role in plasma cell homing and cell adhesion (30,31). In this regard, Hathi et al showed that CRISPR/Cas9 induced depletion of VLA-4 in murine 5TGM1 myeloma cells resulted in increased extramedullary spread to soft tissue sites, liver and spleen and to reduced intramedullary tumor burden compared to mice injected with 5TGM1-wildtype cells where no manifestation of EMD occurred (32). In line with these findings, heparanase-induced shedding of CD138 (Syndecan-1), expressed on normal and malignant plasma cells, promotes myeloma cell migration and invasion by coupling VLA-4 to the vascular endothelial cell growth factor receptor-2 (VEGFR2) (33).…”
Section: Cellular Compartments Of the Tme Bone Marrow Stromal And Vas...mentioning
confidence: 99%
“…One of these drugs is NONOnaproxen, which at a concentration of 0.1 mM, decreases surface activation of β1 integrin on human melanoma M624 cells after one hour of incubation [41]. The combination of β1 and α4 subunits(very late antigen-4 VLA-4, integrin α4β1) is a receptor for vascular cellular adhesion molecule-1 (VCAM-1) [42]. Downregulation of integrin activity leads to diminished melanoma cell adhesion to endothelial VCAM-1.…”
Section: Naproxenmentioning
confidence: 99%